DOI: 10.14264/uql.2015.584
|View full text |Cite
|
Sign up to set email alerts
|

Finite mixture models for regression problems

Abstract: Finite mixture models (FMMs) are a ubiquitous tool for the analysis of heterogeneous data across a broad number of fields including agriculture, bioinformatics, botany, cell biology, economics, fisheries research, genetics, genomics, geology, machine learning, medicine, palaeontology, psychology, and zoology, among many others. Due to their flexibility, FMMs can be used to cluster data, classify data, estimate densities, and increasingly, they are also being used to conduct regression analysis and to analyze r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 274 publications
(463 reference statements)
0
2
0
Order By: Relevance
“…These models are formulated using the conditional mixture and maximum likelihood methodology. The CLR models based on the maximum likelihood methodology are also known as finite mixture models for regression problems [74] and finite mixtures of linear regression [39]. Finite mixture models for regression were discussed in [81].…”
Section: Mixture Modelsmentioning
confidence: 99%
“…These models are formulated using the conditional mixture and maximum likelihood methodology. The CLR models based on the maximum likelihood methodology are also known as finite mixture models for regression problems [74] and finite mixtures of linear regression [39]. Finite mixture models for regression were discussed in [81].…”
Section: Mixture Modelsmentioning
confidence: 99%
“…In this paper we start by considering MGLM [13,14], proposing a semi-parametric estimation of the component inverse link functions for modelling the component conditional expected value of the response variable given explanatory variables. The proposed MSPGLM has several important advantages: In [5], it is shown that under fairly general conditions, √ n consistent estimates of the component parameter directions are obtained.…”
Section: Introductionmentioning
confidence: 99%